Academic Challenges of First-Year Students at the Department of Applied Mathematics and Cybernetics of Baku State University - Guliyeva, Asya; Ismayilova, Khadija; Mammadova, Samira; Mammadov, Zahid (ADA University, 2022)
Every year thousands of students are enrolled in higher education institutes in Azerbaijan. Students enter Universities with certain prior knowledge, personal background, and expectations. At the same time being a first-year student is often associated with numerous challenges to be addressed during the adaptation period. In light of this transition process, the transition from mathematics as a school subject to the scientific discipline is challenging for most math students. This project explores the factors that lead to the first-year math students’ challenges and also, the existing support that those students receive at the Department of Applied Mathematics and Cybernetics of Baku State University. The researchers employed surveys and interviewees to identify the factors that contributed to the academic challenges of the first-year math students, solutions for those challenges, and the support that they would like to receive from the University. The factors that lead to the difficulties of students include a lack of prior knowledge, lack of communication skills, students’ irresponsibility, students’ shyness, lack of time management skills, and low level of foreign languages. The findings of this study highlight that first-year math students receive support from the University, mostly from the administration (dean, deputy dean, tutors) and the instructors of that Department. The research reveals that first-year math students need more support in the adaptation process, related to their low level of prior knowledge and soft skills, the relevance of course material and teaching methods. The support that those students would prefer was having face-to-face lessons and improving teachers' methods, involving young teachers in their education, providing extra classes and additional materials, reducing the number of topics to be taught for one semester, and at the same time explaining the practical side of the lesson. A special type (a mechanism) of support - establishing an Applied Mathematics (AM) Club was suggested depending on the results of the study which aims to assist first-year students and make connections between students and the department staff, and also operate as a social club.
Keywords: Academic challenges.; Academic support.; Academic events.; Social events.; Education